KEPUASAN PASIEN POLIKLINIK PENYAKIT DALAM BERKORELASI DALAM PENERAPAN PROTOKOL KESEHATAN COVID-19 DI SUMATERA BARAT - Mera Delima; Def Primal (Bajang Institute, 2021)
The implementation of the Covid-19 health protocol is carried out to break the chain of the spread of the Covid-19 virus. The implementation of the Covid-19 health protocol one of which is in the hospital so will affect patient satisfaction. Patient satisfaction is the level of patientsâ€™ feelings towards the performance of health services received. This study aims to find out the relationship of the application of protocol health Covid-19 with patient satisfaction in the polyclinic of internal disease, Achmad Darwis Hospital. Research design uses observation sheets for the application of protocol health Covid-19 and patient satisfaction. The study involved 83 respondents. This cross-sectional study obtained analytical observations methods. The research findings had revealed the satisfaction of 70,6% of respondents (p-value â‰¤ 0,05) which means there is a correlation between the implementation of the Covid-19 health protocol and patient satisfaction along with hospitalization. It can be concluded that the implementation of the Covid-19 protocol health is significantly related to patient satisfaction quality which is protecting patients along the caring process in the hospital.